The clinical significance of interleukin‐6 in heart failure: results from the BIOSTAT‐CHF study. (14th May 2019) - Markousis‐Mavrogenis, George; Tromp, Jasper; Ouwerkerk, Wouter; Devalaraja, Matt; Anker, Stefan D.; Cleland, John G.; Dickstein, Kenneth; Filippatos, Gerasimos S.; van der Harst, Pim; Lang, Chim C.; Metra, Marco; Ng, Leong L.; et al.
Abstract : Aims: Inflammation is a central process in the pathophysiology of heart failure (HF), but trials targeting tumour necrosis factor (TNF)‐α were largely unsuccessful. Interleukin (IL)‐6 is an important inflammatory mediator and might constitute a potential pharmacologic target in HF. However, little is known regarding the association between IL‐6 and clinical characteristics, outcomes and other inflammatory biomarkers in HF. We thus aimed to identify and characterize these associations. Methods and results: Interleukin‐6 was measured in 2329 patients [89.4% with a left ventricular ejection fraction (LVEF) ≤ 40%] of the BIOSTAT‐CHF cohort. The primary outcome was all‐cause mortality and HF hospitalization during 2 years, with all‐cause, cardiovascular (CV), and non‐CV death as secondary outcomes. Approximately half (56%) of all included patients had plasma IL‐6 values greater than the previously determined 95th percentile of normal values at baseline. Elevated N‐terminal pro‐brain natriuretic peptide, procalcitonin and hepcidin, younger age, TNF‐α/IL‐1‐related biomarkers, or having iron deficiency, atrial fibrillation and LVEF > 40% independently predicted elevated IL‐6 levels. IL‐6 independently predicted the primary outcome [HR (95% confidence interval) per doubling: 1.16 (1.11–1.21), P  < 0.001], all‐cause mortality [1.22 (1.16–1.29), P  < 0.001] and CV as well as non‐CV mortality [1.16 (1.09–1.24), P  < 0.001; 1.31 (1.18–1.45), P  < 0.001], but did not improve discrimination in previously published risk models. Conclusions: In a large, heterogeneous cohort of HF patients, elevated IL‐6 levels were found in more than 50% of patients and were associated with iron deficiency, reduced LVEF, atrial fibrillation and poorer clinical outcomes. These findings warrant further investigation of IL‐6 as a potential therapeutic target in specific HF subpopulations.